The efficiency of group dynamics and methodical desensitization techniques in marriage counseling to lessen prospective brides and grooms anxiety - Sihotang, Din Oloan; Ginting, Elisa Br; Lumbanbatu, Johannes Sohirimon; Ndona, Yakobus (Universitas Mercu Buana Yogyakarta, 2024)
The purpose of this study is to evaluate how well marriage counseling employs group dynamics and desensitization techniques to lessen prospective brides' and grooms' anxiety. An ABA design is used in this single-subject study. Four people participated in this study: two prospective brides and two prospective grooms. Descriptive analysis is added to visual analysis, also known as visual inspection, in data analysis. The study's findings demonstrate that systematic desensitization techniques combined with relaxation therapy can effectively lower prospective brides' and grooms' anxiety levels. The outcomes both before and after treatment demonstrate this. Counselors and other caregivers may utilize this method as an alternative to help prospective brides and grooms feel less anxious. Keyword: Anxiety; marriage counseling; systematic desensitization.